Korelasi Antara Motivasi Belajar Dan Minat Baca Dengan Prestasi Siswa Menggunakan Metode Apriori: Studi Kasus SMP Negeri 11 Binjai - Muhammad Syamsul Lubis; Katen Lumbanbatu; Imran Lubis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
The quality of education can be achieved by measuring how big the level of success of learning outcomes and achievements obtained by each student. Students who have high achievement are students who have learning motivation and broad knowledge base. By reading, students are expected to have the ability to absorb various knowledge which is mostly conveyed through writing.To get a relationship or correlation between the relationship of one variable with another variable of course required a method in the process of completion. There is a method used by several previous researchers, namely using the association rule method, which is a data mining technique to find associative rules between a combination of items. The algorithm used is a priori which is a step for the process of finding frequent-itemsets by iterating over the data. Where the itemset is the set of items that are in the set processed by the system, while the frequent-itemset shows the itemset that has an occurrence frequency of more than a predetermined minimum value.The objectives of this research are: 1) Build a system that can correlate between learning motivation and interest in reading with student achievement. 2) To find out the minimum support and maximum confidence and the variation between learning motivation and interest in reading and student achievement. 3) To obtain the best rules and produce the latest information. Keywords: Reading Interest, Correlation, Apriori, Data Mining